Hepatitis fulminante por virus herpes simplex tipo 1 - Haddad, Leila; Orozco, Federico; Rosa Diez, Guillermo; Mullen, Eduardo; Valledor, Alejandra; Marciano, Sebastián; Villarroel, Sonia; Barcan, Laura; de Santibañez, Eduardo; Gadano, Adrián (Revista del Hospital Italiano de Buenos Aires, 2011)
.